Tinjauan Yuridis Wanprestasi Sewa Menyewa Tanah (Studi Putusan Pengadilan Negeri Gianyar Nomor 223/Pdt.G/2020/PN Gin) - Sirait, Hilda Angelina; Zaydan, Muhammad Yaseer; Lubis, Rachel; Huda, Genthala Rafik (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Land lease agreements often face various problems, one of the main problems that often arise is default, namely when the tenant cannot fulfill his obligation to pay or fulfill other obligations specified in the lease agreement. The focus of this research is to examine juridically the land lease agreement in Ketewel Village, Gianyar Regency in the decision of the Gianyar District Court Number 223/Pdt.G/2020/PN.Gin. Based on the verdict, the landowner filed a lawsuit because the tenant did not pay the rent in accordance with the agreement made before the Notary. The object of this agreement is a plot of land measuring 2580 m² with a total area of 1280 m² in Ketewel Village, Sukawati District, Gianyar Regency. As a result of the default committed by the tenant, the landowner eventually filed a lawsuit to cancel the lease agreement. This is because there is a clause in the agreement which states that if payment fails to be made twice in a row, the agreement becomes legally void and the money received will belong to the landowner. This research examines the provisions and legal requirements of the agreement, the legal basis for the cancellation of the agreement due to default and the settlement of default in the land lease agreement. This research is qualitative in nature using literature studies and juridical studies. Based on the decision, it can be concluded that the negligence of one of the parties in the land lease agreement can result in the legal cancellation of the agreement. In addition, the party who committed the violation must also pay the court costs incurred due to the violation. This decision not only shows how important it is to fulfill obligations in agreements, but also shows the legal consequences arising from not performing obligations in land lease agreements.